Encyclopedia of Cross-Cultural School Psychology - Clauss-Ehlers, Caroline S.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
With each passing year, the educational landscape continues to become increasingly diversified across race and culture. This poses a significant challenge to schools worldwide$1 (Band particularly to school psychologists and allied educational professionals$1 (Bto recognize and serve the needs of students and families with widely diverse language and cultural backgrounds. To be most effective in their jobs, school psychologists must now have a basic understanding of the impact of language and culture on individual students as well as those they interact with every day. The Encyclopedia of Cross-Cultural School Psychology (ECCSP) is comprehensive and reader friendly, with approximately 400 entries written by leading researchers, educators, and practitioners in the fields of school psychology and education. ECCSP provides an easily accessible A-to-Z reference in one concise volume across these six key cross-cultural competency areas: Legal and Ethical Issues School Culture, Educational Policy, and Institutional Advocacy Psychoeducational Assessment and Related Issues Academic, Therapeutic, and Consultative Intervention Working with Interpreters Research. School psychologists, educators, and other allied child psychology and education professionals, researchers, policy makers, graduate students, healthcare and mental health professionals, child advocates, and paraprofessionals benefit from the way in which this volume highlights the concepts and themes that are critical to addressing cross-cultural issues in schools. Entries also include issues relevant to pre-K through 12th grade and, as a result, provide a lifespan approach to diversity. Each entry offers a definition and description of the term, a bibliography, and additional references for professionals and all readers interested in seeking more in-depth information on any topic. All entries are cross-referenced to other terms of related interest, and a list of contributors is provided at the end of the volume in case readers want to research additional works by the same author. A subject index also helps readers find desired information quickly. ECCSP is certain to become the accompanying reference book for coursework, research, practice, consultation, and policy in the ever-growing field of cross-cultural school psychology and education.s
Keywords: Education; Psychology, clinical; Developmental psychology; Consciousness; Applied psychology; Education; Education (general).; Child and School Psychology; Cross Cultural Psychology; Clinical Psychology; Cognitive Psychology